The impact of physical exercises with weighting in an ascending hierarchical manner in developing some of the physical abilities of judo players under 20-years - Yaqoob, Liza Rustum (International Journal of Psychosocial Rehabilitation, 2020)
One of the important foundations for the success of the training process is its reliance on the scientific method based on physical numbers as well as the selection of correct training methods and means according to the requirements of the judo game, which has physical capabilities in terms of its own laws and decrees. The research problem crystallized through the experience of the field researcher in the field of the game. Some physical abilities related to the level of physical and technical performance, which were demonstrated through field follow-up for judo players under 20 years of age. Therefore, physical exercises were prepared with weighting in an ascending hierarchical manner, which has a noticeable effect during performance and at the best level using maximum effort, less effort than the maximum, and changing the type of exercise And its intensity and campaign, and every aspect of training with heavy resistance (type of exercise, method of training (intensity)) under the title of specific training, and the aim of the research is to identify and prepare physical exercises with weighting in a hierarchical ascending method in developing some physical abilities of judo players under 20 years old. The research shows that physical exercises with weighting in an ascending hierarchical manner has a positive effect on developing some physical abilities of judo players under 20 years of age. The researcher adopted the experimental approach with equal groups and defined the research community as judo players under 20 years of age and by (14) players, and they were prepared and adapted around the standardized training program in terms of the level of performance. And physical exercises with weighting were applied in a hierarchical ascending method in developing some physical abilities on the experimental group for a period of eight weeks and by three training units per week. The researcher used the statistical bag (SPSS). Physical abilities of judo players under 20 years old.